Consumers Psychographic Intention and Purchasing Behavior: A Marketing Framework for Local Tourism Products - Cabaguing, Jordan M.; Lacaba, Teresita Villa G.; Nicart , Analie G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Marketing is an effective tool in promoting and enhancing the image of any tourism destination. If properly planned and implemented, it will provide very good profit and investment. Using descriptive-correlational research, this study explored of determining if there is a significant relationship between consumers' psychographic intention and purchasing behavior, targeted the domestic and international tourists traveling to Guiuan, Eastern Samar and purchasing local products. A convenience sampling method was utilized to determine the number of respondents. There was a total of 332 tourists participated in the study. Frequency counts, percentages, weighted mean, and Pearson’s correlation was used in the analysis of the results. From the findings, it was revealed that consumers are after to quality of products and service delivery. They are particular to price and the value it can give to the amount they paid for. Information about the products must be available online for easy access of information. Accordingly, it is recommended that local government must work with other agencies in assisting how local owners can enhance their delivery of service. Maintaining the culture of hospitality is highly recommended to create a positive image. Consumers’ data must be gathered for reference in future decision-making from their buying patterns and behavioral purchase. The marketing framework will support different local product manufacturers in developing marketing strategies to enhance the marketability of their products and customer loyalty.